Evaluation Method of Regional Water Resources Carrying Capacity Based on Connection Number - DONG Tao (Renmin Zhujiang)
In order to know the carrying capacity of regional water resources and provide reference for regional water resources allocation,this paper selects evaluation indexes from three subsystems of water resources carrying capacity (i.e.,carrying ability system,carrying pressure system and regulation ability system),calculates the subjective weights of evaluation indexes by correcting analytic hierarchy process based on accelerating genetic algorithm (AGA-CAHP),the objective weights of evaluation indexes by projection pursuit based on accelerating genetic algorithm (AGA-PP) and the combined weights of evaluation indexes by the principle of minimum relative information entropy,obtains the connection number of regional water resources carrying capacity by improved set pair analysis based on grey correlation analysis,and then establishes a set pair analysis evaluation model for regional water resources carrying capacity based on entropy principles,combined weights and grey correlation analysis,and finally applies the model in Anhui Province.The results show that the water resources carrying capacity of Anhui Province was in the critical overload from 2005 to 2015,while that was gradually increasing from 2012 to 2015,with the southern region stronger than the northern region.The evaluation results accorded with the actual situation.Therefore,the model can fully integrate the subjective experience information and objective information in the evaluation process,with reasonable results.It has great application value in the comprehensive evaluation of regional resources and environmental carrying capacity.